An approach to the plant body: Assessing concrete and abstract aspects. (September 2021) - Cazalis, Roland; Cottam, Ron
Abstract: The paper aims at proposing a representation of plants as individuals. The first section selects the population of plants to which this study is addressed. The second section describes the effective architecture of plants as modular systems with fixed and mobile elements, in other words, plants and their extensions. The third section presents how plants integrate the fixed and mobile modules into functional units through three areas of particular relevance to plant growth and development: nutrition, defence and pollination. Based on the tangible elements introduced in the previous sections, the fourth section presents the main issue of the proposal which is not apparent at first glance, namely, the local-global relationship in plants' architecture that determines their individuality as organisms. Finally, in the conclusion, we issue the challenge of developing a collective presentation of plants which satisfies their complementary dimension.